2018
DOI: 10.1007/s11846-018-0277-0
|View full text |Cite
|
Sign up to set email alerts
|

An individual-level perspective on intrapreneurship: a review and ways forward

Abstract: Intrapreneurship as a sub-field of entrepreneurship has increased in importance. Due to the crucial role of entrepreneurial employees with regard to innovation and competitive advantage, research has increased and various concepts have emerged. Despite the growing interest in the field, intrapreneurship is still lacking a clear classification of the related concepts as research has thus far been based on diverse theoretical approaches. Indeed, contributions in the field are fragmented, using various definition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
282
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(294 citation statements)
references
References 54 publications
5
282
0
7
Order By: Relevance
“…Pinchot also stated that, intrapreneurs turn ideas into realities inside an organisation. Baruah and Ward (2015) Kuz (2010) Teamwork is frequently utilized as a tool in improving organization-wide cooperation, facilitating idea sharing and thus creating a favourable environment for intrapreneurship to thrive (Eesley and Longenecker, 2006;Blanka, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Pinchot also stated that, intrapreneurs turn ideas into realities inside an organisation. Baruah and Ward (2015) Kuz (2010) Teamwork is frequently utilized as a tool in improving organization-wide cooperation, facilitating idea sharing and thus creating a favourable environment for intrapreneurship to thrive (Eesley and Longenecker, 2006;Blanka, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars, such as Blanka (2018), Odor (2018), McDowells (2017), Otsu (2016), Moriano, Molero, Topa and Levy (2014), Witzell (2014) and Webb (2013) studied the concepts of organizational culture and intrapreneurship growth in isolation. In their findings, they revealed that organizational culture is important to an organizational performance and that intrapreneurship is of great importance to how innovative an organization would be.…”
Section: Introductionmentioning
confidence: 99%
“…New venture creation, the transformation of activities, and up-gradation of strategy are the organisational functions of intrapreneurship or CE (Stopford & Baden-Fuller, 1994). Differing roles of engineering firms from other corporations have effects on the intrapreneurial capacities of employees (Blanka, 2018). The nature of engineering jobs sometimes restricts risk-taking by employees due to fear of failure.…”
Section: Introductionmentioning
confidence: 99%
“…Intrapreneurship (entrepreneurship in existing companies) in small and medium-sized firms (SMEs) is based on the decisions of entrepreneurs and is also important for the business performance of enterprises. Intrapreneurship may be seen as a concept at the individual level [9]. To engage or not to engage in intrapreneurship (entrepreneurial behavior) is a personal decision [19], [23].…”
Section: Introductionmentioning
confidence: 99%